Peningkatan Keahlian Teknis Petani Melalui Pendidikan Vokasional Agribisnis Berbasis Proyek di Desa Tejo Agung - Bambang Irawan; Citra Rianzani; Astri Shabrina; Dini Destya Tamara (Wisanggeni: Jurnal Pengabdian Masyarakat, 2022)
Abstract: This study aims to describe the improvement of farmers’ technical skills through project-based vocational agribusiness education using the Asset-Based Community Development (ABCD) approach in Tejo Agung Village, 2023. Using a qualitative method, data were collected through observation, interviews, and documentation. The results show that the ABCD approach effectively empowered farmers to identify and utilize local assets such as organic waste, home yards, and social networks. Through hands-on training projects like compost production and horticulture, farmers improved their technical abilities and developed independence, collaboration, and agribusiness awareness. The program positively impacted both individual skills and the overall empowerment of the farming community.